PERFORMANCE OF RED SKINNED POTATO VARIETIES/HYBRIDS IN RAINFED CONDITION OF MEGHALAYA - Gupta, V K.; Pandey, S K.; Kumar, Manoj; Manivel, P; Das, B. K.; Gogoi, M. B.; Kumar, Shantanu; Baishya, L. K. (Potato Journal, 2013)
Two red skinned hybrids (MP/92-56 and MS/92-2105 along with three red skinned (Kufri Kanchan, Kufri Lalima and Desiree) and two white skinned (Kufri Jyoti and Kufri Giriraj) commercial cultivars as checks were evaluated for growth parameters, yield and disease reaction against late blight at Shillong during 2003 and 2004. Germination percentages at 45 days after planting (DAP) ranged from 65.58 to 98.34% and 87.90 to 99.15% in 2003 and 2004, respectively. The germination percentage was also affected significantly by year and their interaction with genotypes (Y x V). The mean maximum germination percentage was recorded in cv. Kufri Lalima (98.53%) and minimum in Desiree (81.33%). There was a significant difference between genotypes for mean plant height and cv. Kufri Kanchan had maximum plant height (76.12 cm) at 75 DAP, where as cv. Kufri Jyoti had the minimum(58.25 cm). However, the effect of year and interaction between genotype and year on mean plant height was nonsignificant. Area under disease progress curve (AUDPC) indicated that there was significant difference among the genotypes and the years. The least (210.87) and highest (537.40) mean AUDPC values were recorded in cvs. Kufri Giriraj and Kufri Jyoti, respectively. Among the red skinned cultivars/hybrids, the least mean AUDPC value was recorded in cv. Kufri Kanchan (238.58) followed by the processing hybrid MP/92-56 (315.44) and cv. Kufri Lalima(385.59). However, the yields of the red skinned varieties were not positively correlated with their blight resistance (AUDPC). Mean total tuber yield pooled over years indicated that white skinned cultivars Kufri Giriraj (213.91 q/ ha) and Kufri Jyoti (165.21 q/ha) performed significantly best. Among the red skinned cultivars/hybrids cv. Kufri Lalima (135.55 q/ha) was found to be significantly superior over Desiree (132.90 q/ha) and cv. Kufri Kanchan(77.05 q/ha). However, there was a significant difference in the total tuber yield obtained from different genotypes during both the years and their interactions.